2021
DOI: 10.15252/embj.2021108249
|View full text |Cite
|
Sign up to set email alerts
|

SARS‐CoV‐2 nucleocapsid suppresses host pyroptosis by blocking Gasdermin D cleavage

Abstract: SARS‐CoV‐2 is an emerging coronavirus that causes dysfunctions in multiple human cells and tissues. Studies have looked at the entry of SARS‐CoV‐2 into host cells mediated by the viral spike protein and human receptor ACE2. However, less is known about the cellular immune responses triggered by SARS‐CoV‐2 viral proteins. Here, we show that the nucleocapsid of SARS‐CoV‐2 inhibits host pyroptosis by blocking Gasdermin D (GSDMD) cleavage. SARS‐CoV‐2‐infected monocytes show enhanced cellular interleukin‐1β (IL‐1β)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
75
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(86 citation statements)
references
References 52 publications
(79 reference statements)
2
75
1
1
Order By: Relevance
“…Coincidentally, during our revision process, the latest study demonstrated that SARS-CoV-2 nucleocapsid protein associates with hGSDMD in cells and inhibits hGSDMD cleavage in vitro and in vivo . SARS-CoV-2 nucleocapsid directly binds the linker region of GSDMD to protect GSDMD tetrapeptide from being cut by caspase-1 ( 57 ). This indicates that other proteins of coronaviruses also participate in suppressing GSDMD-mediated pyroptosis.…”
Section: Discussionmentioning
confidence: 99%
“…Coincidentally, during our revision process, the latest study demonstrated that SARS-CoV-2 nucleocapsid protein associates with hGSDMD in cells and inhibits hGSDMD cleavage in vitro and in vivo . SARS-CoV-2 nucleocapsid directly binds the linker region of GSDMD to protect GSDMD tetrapeptide from being cut by caspase-1 ( 57 ). This indicates that other proteins of coronaviruses also participate in suppressing GSDMD-mediated pyroptosis.…”
Section: Discussionmentioning
confidence: 99%
“…High throughput metagenomic sequencing and pathway analysis of cells obtained from the upper airway of patients with early Covid-19 infection showed a major suppression of inflammatory responses notably of genes mediating inflammasome priming and monocyte/macrophage recruitment. Interestingly, recent work has suggested inflammasome suppression by the Sars-Cov-2 nucleocapsid protein because of impaired GSDMD cleavage 40 . Together these studies strongly suggest an immunosuppressive effect of early Covid-19 infection, mediated in part by the viral E protein, that is permissive to continued viral replication leading to high viral titers increasing infectiousness and potential downstream adverse effects to the host.…”
Section: Discussionmentioning
confidence: 99%
“…Because NLRP3 inflammasome formation is unaffected by SARS-CoV-2 nucleocapsid protein, the natural consequence of GSDMD protection is the intracellular accumulation of IL-1β and IL-18 that cannot be released. This mechanism could therefore delay the initial antiviral response and contribute to the asymptomatic phase of COVID-19 infection (298). Opposing this evidence, multiple studies have in contrast shown that the inflammasome is activated in COVID-19 patients, linking this activation to a more severe disease (299)(300)(301).…”
Section: Sars-cov-2 Suppression Of the Inflammasome And Pyroptosismentioning
confidence: 99%